Diagnosis of the technical training process in Olympic wrestling/Diagnóstico del proceso de formación técnica en la lucha olímpica - Vladimir Antonio González Cabrera; José Enrrique Carreño Vega; Abel Gallardo Sarmiento; Bertha Susana Paz-Susana; Jorge Vinicio Morales Tierra (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: International and national organizations demand a training process that facilitates access to technical knowledge, from modern teaching methods , that is inclusive, equitable and of quality. Objective: In response to this, the research was aimed at diagnosing the current state of the technical training process of Olympic wrestling. Materials and methods: For this purpose, a longitudinal study was carried out from 2012 to 2021, selecting 18 managers, 59 wrestlers and 24 coaches as a sample. Two mobile phones were used to record and obtain the images of the combats, from where the observations of the technique were made. The methods used were the dialectical-materialist, as well as those of a theoretical and empirical nature, highlighting the review of documents, the interview, the survey and the observation, while as a verification tool the methodological triangulation, fundamental in the process of describing the object of study. Results: The applied procedures determined the existence of difficulties in the pedagogical-sports direction, the scientific-technical content system and the analysis of key factors of the technique, especially, with handling of the action model (video library), the video -analysis (execution parameters), the common factor (selection of successful and unsuccessful cases) and working documents (technical sheets and comparison list). Conclusions: Finally, the guidelines of a didactic model for the trainig of the technique are declared, based on a systemic elaboration of the scientific-technical contents and the analysis of key factors, considering the information and communication technologies (ICT).